Pandangan Mahasiswa terhadap Hambatan pada Pelaksanaan Skill Lab di Fakultas Kedokteran Universitas Andalas - Hardisman Hardisman; Yulistini Yulistini (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Skills lab is a clinical skill training using model and simulation, which is very important in the learning process to develop clinical skill competencies of medical students. Through the process, the next step of learning on real patients will be safer and more effective. The study was conducted to explore learning barriers of medical students in the skill lab training to obtain experiences and competencies.Method: A qualitative study was conducted to explore the problems using in-depth interview as method of data collection. Thematic analysis was used to analyze the data. The respondents of the study were 46 medical students in semester V and VII in the Faculty of Medicine, Andalas University.Results: The main barriers that the students faced were clinical instructor factors, such as late attendance and replacement time with shorter allocation. Due to these factors, the students could not obtain optimal learning process, supervision and required competencies. Other factors such as lack of simulation model and limited time had also significant impact.Conclusion: Learning barriers of skill lab training were caused by multi factors. Therefore, systematic arrangement, facility and assessment, and the quality of instructors’ performance need to be improved.